2013
DOI: 10.1148/radiol.12121460
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Acute Kidney Injury Following Intravenous Contrast Medium Administration: A Systematic Review and Meta-Analysis

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.12121460/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
219
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(248 citation statements)
references
References 51 publications
16
219
0
13
Order By: Relevance
“…Meta-analysis of 13 studies in which incidence of AKI was directly compared between patients who were and were not exposed to CM failed to demonstrate any increased risk of AKI, dialysis, or death associated with CM [9]. This is supported by a recent nationwide analysis of administrative data for almost 6 million patients in the USA, where rates of AKI were nearly identical in patients who did and did not receive CM [10].…”
Section: Intravenous Contrast Media and Acute Kidney Injury In The Gementioning
confidence: 91%
“…Meta-analysis of 13 studies in which incidence of AKI was directly compared between patients who were and were not exposed to CM failed to demonstrate any increased risk of AKI, dialysis, or death associated with CM [9]. This is supported by a recent nationwide analysis of administrative data for almost 6 million patients in the USA, where rates of AKI were nearly identical in patients who did and did not receive CM [10].…”
Section: Intravenous Contrast Media and Acute Kidney Injury In The Gementioning
confidence: 91%
“…Therefore, the existence of a causal relationship is not clear. In a systematic review/meta‐analysis performed in 2013, McDonald et al .,42 found that the relative risk (RR) of acute kidney injury (AKI) development, requiring intermittent hemodialysis, and mortality were 0.79, 0.88, 0.95, respectively, and no significant differences were observed (15582 patients exposed to contrast agents, 10368 patients not exposed.). Ng et al 43.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-enhanced computed tomography (CT) is the gold standard for diagnosis and assessment of severity of acute pyelonephritis (APN) and its complications [6]; it is however burdened by the well-known risk of contrast medium-induced nephropathy [7][8][9] CEUS has been shown to perform well in the diagnosis of APN for both native and transplanted kidneys [10,11], but its use requires specific expertise not so widely diffused. Magnetic resonance imaging (MRI) is indicated for patients with contraindications to iodinated contrast media such as transplant recipients.…”
mentioning
confidence: 99%